The Role of Universities in Education 5.0 towards Lifelong Learning - Nguyễn Song Hảo (Journal of Technical Education Science, 2025)
This study aims to identify the role of universities in the context of education 5.0, with the goal of building a high-quality workforce that is ready to learn throughout whole life to develop the country. The study emphasizes that, in the era of education 5.0, universities are not only places to provide knowledge but also centers of lifelong learning, where learners are encouraged and supported to develop their adaptability and creativity in a rapidly changing world. This role not only contributes to individual success but also promotes the sustainable development of society. The study also proposes recommendations to create a flexible learning environment, develop personalized learning programs, encourage self-learning and apply technology in the training process. These proposals aim to personalize the learning process, helping learners not only acquire knowledge but also develop critical thinking, creativity and self-management learning skills, thereby building a lifelong learning culture, contributing to the prosperous development of society in the era of education 5.0.